Effect of Meniscal Ramp Lesion Repair on Knee Kinematics, ACL In-Situ Forces and Bony Contact Forces – A Biomechanical Study. Issue 6 (28th June 2019) - Pfeiffer, Thomas; Naendrup, Jan-Hendrik; Nagai, Kanto; Novaretti, Joao; Chan, Calvin; Debski, Richard; Musahl, Volker
Aims and Objectives: While recent studies showed that all inside meniscal ramp repair is able to restore knee kinematics, the effects of ramp repairs on ACL in-situ forces and bony contact forces is still unclear. Therefore, the purpose of this study is to determine the effect of ramp lesion repair on knee kinematics, the ACL-ISF and bony contact forces using a 6-degree-of-freedom (DOF) robotic testing system. It was hypothesized that ramp repair will restore kinematics, ACL-ISF and bony contact forces comparably to the forces of the intact knee. Materials and Methods: Nine fresh-frozen human cadaveric knee specimens were tested using a 6-degree-of-freedom robotic testing system (FRS2010) to continuously flex the knee from full extension to 90° and apply continuous loading conditions: 1) 90 N of anterior force, 2) 5 Nm of external rotation torque, 3) 134 N anterior force + 200 N compression force, 4) 4 Nm external rotation torque + 200 N compression force, 5) 4 Nm internal rotation torque + 200 N compression force. Loading conditions were applied to the intact knee, a knee with an arthroscopically induced 25 mm ramp lesion, and a knee with an all-inside repaired ramp lesion. ACL in-situ forces, medial compartment bony contact forces and lateral compartment bony contact forces were quantified. Repeated measure ANOVAs were performed to compare knee states at each flexion angle (p<0.05). Results: In response to all loading conditions, no differences with respect to kinematics, ACL in-situ forces, and bony contact forces between the intact state and the ramp lesion state were detected. However, compared to the intact state, ramp lesion repair significantly reduced anterior translation in flexion angles from full extension to 40° in response to 5 N anterior force (p < 0.05). In addition, a significant decrease in the ACL in-situ forces after ramp repair was detected only for higher flexion angles when 4 Nm external rotation torque combined with 200 N compression force (p < 0.05) and when 4 Nm internal rotation torque combined with 200 N compression force were applied (p < 0.05). Conclusion: In this biomechanical study, ramp lesions did not significantly affect knee biomechanics. Care must be taken to avoid potential overconstraint when performing all-inside ramp lesion repairs. From biomechanical time-zero perspective, it is debatable if stable ramp lesions need to be addressed surgically. As stable ramp lesions do not significantly change knee biomechanics, the indications for ramp lesion repair may be limited.